HOW SOCIAL MEDIA MARKETING ACTIVITIES DRIVE REPURCHASE INTENTION: THE ROLE OF BRAND TRUST AND BRAND ATTACHMENT - Sherli Afifatul Ayiyah; Mohamad Rifqy Roosdhani (Universitas Sarjanawiyata Tamansiswa, 2026)
Generation Z's skincare habits have been shaped by social media. The corporation uses social media to establish customer connections and drive repurchase. This research examines how social media marketing activity affects repurchase intention in Indonesian Gen Z via brand trust and attachment to Skintific goods. The quantitative research surveyed Skintific product buyers using questionnaires. Purposive sampling yielded 210 responses. SmartPLS 4 was used to analyze data using PLS-SEM. Social media marketing improved brand trust, attachment, and repurchase intention significantly. Brand trust and attachment both increase repurchase intention and influence the link between social media marketing activity and Gen Z consumers' repurchase intentions.